Two Cases of Lacaziosis in Bottlenose Dolphins (Tursiops truncatus) in Japan - Keiichi Ueda; Ayako Sano; Jyoji Yamate; Eiko Itano Nakagawa; Mitsuru Kuwamura; Takeshi Izawa; Miyuu Tanaka; Yuko Hasegawa; Hiroji Chibana; Yasuharu Izumisawa; Hirokazu Miyahara; Senzo Uchida (Case Reports in Veterinary Medicine)
Lacaziosis, formerly called lobomycosis, caused by Lacazia loboi, is a zoonotic mycosis found in humans and dolphins and is endemic in the countries on the Atlantic Ocean. Although the Japanese coast is not considered an endemic area, photographic records of lacaziosis-like skin lesions were found in bottlenose dolphins (Tursiops truncatus) that were migrating in the Goto Islands (Nagasaki Prefecture, Japan). We diagnosed 2 cases of lacaziosis in bottlenose dolphins captured simultaneously at the same coast within Japanese territory on the basis of clinical characteristics, cytology, histopathology, immunological tests, and detection of partial sequences of a 43 kDa glycoprotein coding gene (gp43) with a nested-PCR system. The granulomatous skin lesions from the present cases were similar to those found in animals from endemic areas, containing multiple budding and chains of round yeast cells and positive in the immune-staining with anti-Paracoccidioides brasiliensis serum which is a fungal species related to L. loboi; however, the gp43 gene sequences derived from the present cases showed 94.1% homology to P. brasiliensis and 84.1% to L. loboi. We confirmed that the causative agent at the present cases was different genotype of L. loboi from Amazon area.